The second-generation ALK inhibitor alectinib effectively induces apoptosis in human neuroblastoma cells and inhibits tumor growth in a TH-MYCN transgenic neuroblastoma mouse model. (1st August 2017) - Lu, Jiaxiong; Guan, Shan; Zhao, Yanling; Yu, Yang; Woodfield, Sarah E.; Zhang, Huiyuan; Yang, Kristine L.; Bieerkehazhi, Shayahati; Qi, Lin; Li, Xiaonan; Gu, Jerry; Xu, Xin; et al.
Abstract: Activating germline mutations of anaplastic lymphoma kinase (ALK) occur in most cases of hereditary neuroblastoma (NB) and the constitutively active kinase activity of ALK promotes cell proliferation and survival in NB. Therefore, ALK kinase is a potential therapeutic target for NB. In this study, we show that the novel ALK inhibitor alectinib effectively suppressed cell proliferation and induces apoptosis in NB cell lines with either wild-type ALK or mutated ALK ( F1174L and D1091N ) by blocking ALK-mediated PI3K/Akt/mTOR signaling. In addition, alectinib enhanced doxorubicin-induced cytotoxicity and apoptosis in NB cells. Furthermore, alectinib induced apoptosis in an orthotopic xenograft NB mouse model. Also, in the TH -MYCN transgenic mouse model, alectinib resulted in decreased tumor growth and prolonged survival time. These results indicate that alectinib may be a promising therapeutic agent for the treatment of NB. Highlights: Alectinib treatment strongly induces apoptosis in human neuroblastoma cells. Alectinib inhibits neuroblastoma tumorigenesis. Alectinib effectively inhibits the activity of wild-type and mutated ALK in neuroblastoma cells.